Clinical and Epidemiological Characteristics of Infants - Mohammad Faranoush; Ibrahim Qaddoumi; Azim Mehrvar; Hadi Musakhani; Morteza Ashrafi; Narjes Mehrvar; Mithra Ghalibafian; Mahyar Nourian (Journal of Pediatric Hematology/Oncology, 2026)
Background: Malignancies in infants younger than 6 months differ from those in older children in incidence, clinical presentation, treatment response, and outcomes. Limited data exist on these infants’ survival, particularly in low- and middle-income countries. Procedure: We retrospectively analyzed the data of 153 infants (